Weak and strong forms of irresolute maps - Miguel Caldas, Cueva (Hindawi Limited, 2018)
We consider new weak and stronger forms of irresolute and semi-closure via the concept sg-closed sets which we call ap-irresolute maps, ap-semi-closed maps and contra-irresolute and use it to obtain a characterization of semi-T1/2 spaces.